Thermo-sensitive hydrogel combined with SHH expressed RMSCs for rat spinal cord regeneration - Gu, Jun; Gao, Biao; Zafar, Hajra; Chu, Bo; Feng, Xiaojun; Ni, Yinjie; Xu, Lin; Bao, Rui (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: Spinal cord injury (SCI) has a damaging impact on patients, amid being a worldwide problem with no effective treatment. Herein, we reported a method for functional therapy of SCI in rats, wherein we combined thermo-sensitive hydrogel with Sonic Hedgehog (SHH) expressed in rat bone-marrow derived mesenchymal stem cells (RMSCs). Methods: Bone marrow-derived mesenchymal stem cells (BMSCs) were isolated from Sprague-Dawley (SD) female rats. The SHH was optimized and transferred into RMSCs via cationic liposomes, while thermo-sensitive hydrogel was reformed with hyaluronate (HA) and Pluronic F127. Then, SCI rat model was accordingly established by male SD rats and randomized into sham, model, RMSCs with hydrogel and SHH-RMSCs with hydrogel. The evaluation of SCI repair based on Basso, Beattie Bresnahanlocomotor rating scale (BBB scale) and inclined plate score. Immunofluorescence, immunohistochemistry and hematoxylin-eosin were utilized to explore the expression of protein (GFAP, GAP43, NF200 and MBP) and histopathology. Results: It was demonstrated that transfection of SHH with cationic liposomes exhibited more effect in RMSCs than lipofectamine 2000. As shown in SEM, 3.5 % HA-F127 demonstrated porous structure. In the MTT and dead/live assay, 3.5 % HA-F127 showed good biocompatibility for RMSCs. Both RMSCs and SHH-RMSCs groups could significantly promote BBB and inclined plate scores (P < 0.01) compared with the model. Besides, SHH-RMSCs group was significantly improved than RMSCs with the expression of related proteins, wherein NF200, MBP and GAP43 were principally enhanced with GFAP expression being virtually down regulated. Conclusion: All in all, the results suggested that transplantation of RMSCs with SHH could improve the function of SCI and promote nerve regeneration.